2018
DOI: 10.1016/j.ijrobp.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Radiation Therapy and Survival in Clinically Node-Positive Prostate Cancer

Abstract: SummaryThe survival benefit of combined radiation therapy and androgen deprivation therapy compared with androgen deprivation therapy alone for clinically lymph nodee positive prostate cancer remains controversial. We identified clinically nodepositive, nonmetastatic prostate cancer patients from the Veterans Affairs system and compared mortality outcomes between treatment groups. We found that definitive treatment with radiation therapy improved prostate cancerespecific mortality and all-cause Purpose: The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Cervical cancer with para-aortic lymph node involvement used to be considered M1 disease, 16 but multiple studies have shown good oncologic outcomes with definitive local treatment, [17][18][19] resulting in an eventual shift of paraaortic lymph node involvement to be considered regional nodal disease. 2 Similar findings have been shown in nodepositive [20][21][22] and distant metastatic prostate cancer. 23 The role for definitive RT, generally with chemotherapy, in the management of unresectable vulvar cancer is well documented from multiple prospective studies, 15,24 with contemporary series showing feasibility of using advanced techniques with good oncologic outcomes in well-selected patients.…”
Section: Discussionsupporting
confidence: 66%
“…Cervical cancer with para-aortic lymph node involvement used to be considered M1 disease, 16 but multiple studies have shown good oncologic outcomes with definitive local treatment, [17][18][19] resulting in an eventual shift of paraaortic lymph node involvement to be considered regional nodal disease. 2 Similar findings have been shown in nodepositive [20][21][22] and distant metastatic prostate cancer. 23 The role for definitive RT, generally with chemotherapy, in the management of unresectable vulvar cancer is well documented from multiple prospective studies, 15,24 with contemporary series showing feasibility of using advanced techniques with good oncologic outcomes in well-selected patients.…”
Section: Discussionsupporting
confidence: 66%
“…1 Several studies have shown that addition of local treatment (surgery and RT) to ADT improves treatment outcome. [2][3][4][5][6][7][8][9] Thus, in the NCCN guideline 2018, external beam RT combined with ADT ± abiraterone and prednisone is regarded as one of the standard therapies along with ADT ± abiraterone and prednisone. 1 The guideline further recommends nodal radiation and dose escalation to clinically positive nodes considering the tolerance dose of surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
“…1 Recently, some retrospective and database studies have demonstrated the benefits of adding definitive local treatment including radical prostatectomy (RP) and/or RT to ADT for cN1 patients. [2][3][4][5][6][7][8][9] However, the appropriate radiation field and its dose have not been well determined. Some studies include pelvic nodal area 4,7,9 and others include only the prostate and seminal vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 gives an overview of prospective trials evaluating the value of whole pelvis radiotherapy in four different settings: (1) patients with cN0 (clinically node negative) disease and a substantial risk (term varies largely between studies) 1,3,7,8,11,14,20,24 of pathologically involved nodes in the primary setting, (2) patients with cN1 (clinically node positive) disease in the primary setting, [25][26][27][28][29][30][31] (3) patients with adjuvant pN1 (pathologically node positive) disease in the postoperative setting, 12,[32][33][34][35][36][37] and (4) patients with pNx (unknown node status) and pN0 (pathologically node negative) disease in the postoperative salvage setting. [38][39][40] Patients with cN0 disease in the primary setting…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…When suspected positive pelvic nodes are present on CT imaging, adding whole pelvis radiotherapy to androgen deprivation therapy significantly improves survival. [25][26][27]31 With the advent of modern biological imaging techniques, such as PSMA PET-CT, the likeli hood that pelvic nodes will be found earlier, more frequently, and will be more widespread is high, as shown in several trials. 27,[42][43][44][45] In patients with cN1 disease in the primary setting, androgen deprivation therapy is standard management and, in our opinion, whole pelvis radio therapy should always be added, including the application of a simultaneously integrated boost to PSMA PET-positive nodes.…”
Section: Patients With Cn1 Disease In the Primary Settingmentioning
confidence: 99%